Assessing window area and potential for electricity savings by using daylighting and hybrid ventilation in office buildings in southern Brazil. (November 2017) - Rupp, Ricardo Forgiarini; Ghisi, Enedir
The aim of this study is to develop a method to assess window area based on electricity consumption in office buildings in southern Brazil. The method may be used in the preliminary building design process in order to help choose an adequate window area to minimize its impact on energy consumption, depending on climate, building size, solar orientation, and mode of operation. The method also considered thermal comfort and daylighting performance. Four cases were investigated: Case 1, building operating with artificial lighting and air-conditioning; Case 2, considering integration of daylight and artificial light with air-conditioning; Case 3, building operating with hybrid ventilation and artificial lighting; and Case 4, considering integration of daylight and artificial light with hybrid ventilation. EnergyPlus and Daysim simulation programs were used to estimate the electricity consumption for each model. The integration of daylighting with artificial light (Case 2) generates more potential for energy savings (PES) than hybrid ventilation (Case 3). Case 4 showed PES ranging from 4.2% to 64.9%, allowing larger window areas with lower consumption, resulting in the highest PES.